The Role of the Mandailing Natal Regency Transportation Office in Increasing Regional Original Revenue (PAD) Parking Management in Panyabungan City - Lubis, Harianto; Ritonga, Syafruddin; Junita, Audia (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The low parking revenue in Mandailing Natal Regency over the past two years has hurt Regional Original Revenue (PAD). Observations show that this problem is caused by a lack of public awareness of paying parking fees and a lack of knowledge about parking services. This study aims to analyze the role of the Mandailing Natal Regency Transportation Office in increasing PAD through parking management in Panyabungan City. The approach used is qualitative with descriptive type, and data is collected through observation, interviews, and documentation conducted at the Transportation Agency office. The results showed that the agency has three leading roles in parking management to increase PAD: planning, mobilizing, and supervising. However, internal and external obstacles complicate parking management, such as the lack of parking lots in Panyabungan City that could disrupt nearby shops and the unavailability of terminals for rural transportation and buses. Therefore, although the role of the Transportation Agency is already underway, further optimization is needed to increase PAD through better parking management in Panyabungan City.